2022
DOI: 10.7759/cureus.28006
|View full text |Cite
|
Sign up to set email alerts
|

Biclonal Desmoid-Type Fibromatosis With Two Beta-Catenin Mutations: Evidence for the Recruitment of Normal Myofibroblasts

Abstract: Sporadic aggressive fibromatosis, or desmoid-type fibromatosis, is characterized by oncogenic mutations in CTNNB1. The clonal cell is a myofibroblast-like cell, and it has been hypothesized that the recruitment of normal myofibroblasts could contribute significantly to the tumor. We describe a case in which a CTNNB1 p.T41A mutation was present at a mutant allele frequency of 30%, suggesting that a significant proportion of the tumor myofibroblasts may have been recruited from normal precursor pools. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Our two cases in which the DTF tracked along nerves both had an S45F mutation. Given that one report of three patients found identical CTNNB1 mutations in the NMC lesion and also the associated NMC-DTF, Carter et al have suggested that a CTNNB1-mutated myofibroblast precursor can be induced to proliferate by a trigger, similar to typical DTF [3,16,18,19,27,28]. One study described ultrasound characteristics of NMC in seven patients [28]; CTNNB1 mutation was reported in one as S45F [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our two cases in which the DTF tracked along nerves both had an S45F mutation. Given that one report of three patients found identical CTNNB1 mutations in the NMC lesion and also the associated NMC-DTF, Carter et al have suggested that a CTNNB1-mutated myofibroblast precursor can be induced to proliferate by a trigger, similar to typical DTF [3,16,18,19,27,28]. One study described ultrasound characteristics of NMC in seven patients [28]; CTNNB1 mutation was reported in one as S45F [28].…”
Section: Discussionmentioning
confidence: 99%
“…A model of DTF pathogenesis involves an activation stimulus in the setting of dysregulation of the Wnt/beta-catenin pathway resulting in beta-catenin upregulation, nuclear translocation, and increased Wnt target gene expression resulting in cell proliferation and extracellular matrix (ECM) production [ 2 , 3 , 8 ]. Other signaling molecules associated with this process may also recruit normal non-clonal myofibroblast precursor cells such as prophylactic ADAM12 positive cells from a PDGFR-positive precursor pool, thus adding normal non-clonal myofibroblasts to the true DTF myofibroblasts [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic DTF usually has a mutation in CTNNB1, the gene that encodes beta-catenin. Rare cases of DTF have been reported that lack an identified mutation in CTNNB1 or APC [4][5][6][7] and cases with more than one mutation in CTNNB1 have been reported (reviewed in [8]).…”
Section: Introductionmentioning
confidence: 99%